2019
DOI: 10.1016/j.bbmt.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Challenge to Predict Mobilized Peripheral Blood Stem Cells on the Fourth Day of Granulocyte Colony-Stimulating Factor Treatment in Healthy Donors: Predictive Value of Basal CD34+ Cell and Platelet Counts

Abstract: , prospective, observational, single-center cohort study on healthy donors was designed to identify predictors of CD34 + cell mobilization on day 4 after granulocyte colony-stimulating factor (G-CSF) administration. As potential predictors of mobilization, age, sex, body weight, height, blood volume, WBC count, peripheral blood (PB) mononuclear cell count, platelet (Plt) count, and hematocrit and hemoglobin levels were considered. Two different evaluations of CD34 + cell counts were determined for each donor: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In a study by Basak et al, no correlation was found between CD34+ cell dose and WBC count on the first day of plerixafor injection (30), which is inconsistent with our results. CD34+ cell count before collection is the most accurate and reliable predictor of mobilization rate (25,31,32), which is also confirmed by the present study's data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a study by Basak et al, no correlation was found between CD34+ cell dose and WBC count on the first day of plerixafor injection (30), which is inconsistent with our results. CD34+ cell count before collection is the most accurate and reliable predictor of mobilization rate (25,31,32), which is also confirmed by the present study's data.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Martino et al supports the significant effect of platelet count before G-CSF administration in healthy donors on the quantity of collected CD34+ cells (25). In another study, low platelet counts before apheresis in patients with multiple myeloma were significantly associated with poor mobilization outcomes (26).…”
Section: Discussionmentioning
confidence: 86%
“…Considering demographic data and CBC parameters, our algorithm did not reveal a reliable tool to identify poor mobilizers before G-CSF application [ 6 ]. Besides genetic polymorphisms, other parameters (e.g., basal CD34+ count) might also be useful predictors of mobilization performance [ 28 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 studies that assessed the association between CD34 + cell yield and donor gender 12 (71%) reported higher CD34+ cell yields in males (9, 10, 12, 14, 1719, 25, 28, 30, 43, 44) but the remaining five studies (29%) found no association (6, 15, 16, 24, 29). Of the 20 studies that assessed blood CD34+ cell concentration, eight (42%) reported higher concentrations in males (9, 30, 32, 34, 36, 37, 39, 45) whereas 12 (59%) reported no significant effect of gender (6, 17, 21, 22, 31, 33, 35, 38, 4042, 46).…”
Section: Resultsmentioning
confidence: 99%
“…Seven of nine studies reported an association between high BMI and higher blood CD34+ concentration (6, 26, 30, 32, 37, 42, 46). None of the seven studies that assessed donor height reported an association with either CD34+ cell yield (20, 25, 29), or blood CD34+ cell concentration (36, 38, 40, 41). All four of the studies that assessed the differences in weight between donor and recipients reported an association between donors having greater positive weight differences and higher CD34 + cell yield (6, 8, 14, 28).…”
Section: Resultsmentioning
confidence: 99%